A Geometric Aspect of the Two-Parameter Planar Lorentzian Motions. (19th September 2018) - Şentürk, Gülsüm Yeliz; Yüce, Salim
Abstract : We examined the moving coordinate systems, the polar axes, the density invariance of the polar axis transformation, and the curve plotter points and the support function of the two-parameter planar Lorentzian motion. Furthermore, we were concerned with the determination of the motion using the polar axes and analyzed the motion when the density of the polar axes is zero.